1990
DOI: 10.1136/adc.65.10_spec_no.1067
|View full text |Cite
|
Sign up to set email alerts
|

Gut blood flow velocities in the newborn: effects of patent ductus arteriosus and parenteral indomethacin.

Abstract: The effects on gut blood flow velocities of parenteral indomethacin (0-2 mg/kg) given either quickly as a bolus or slowly as an infusion were compared in consecutive studies of two groups of infants with symptomatic patent ductus arteriosus. In the presence of patent ductus arteriosus the range of velocities in the superior mesenteric artery before indomethacin was given was characterised by pronounced abnormalities including absent-or in some cases even retrograde-diastolic flow.In eight subjects the first ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
2
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(87 citation statements)
references
References 23 publications
0
81
2
4
Order By: Relevance
“…Indomethacin is associated with an increased incidence of intestinal bleeding and perforations in the preterm infant [41][42][43][44][45]. Coombs et al [2] and Van Bel et al [3] noted a significant reduction in superior mesenteric artery blood flow velocity in preterm infants receiving indomethacin. Meyers et al [4] reported that indomethacin at a dose of 0.3 mg/kg significantly reduced terminal ileal blood flow in near-term fetal lambs, and impaired the ability of the terminal ileum to autoregulate its oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indomethacin is associated with an increased incidence of intestinal bleeding and perforations in the preterm infant [41][42][43][44][45]. Coombs et al [2] and Van Bel et al [3] noted a significant reduction in superior mesenteric artery blood flow velocity in preterm infants receiving indomethacin. Meyers et al [4] reported that indomethacin at a dose of 0.3 mg/kg significantly reduced terminal ileal blood flow in near-term fetal lambs, and impaired the ability of the terminal ileum to autoregulate its oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, indomethacin was associated with a significant decline in the levels of oxidized cytochrome oxidase, reflecting a reduction in cerebral oxygenation [14]. Interestingly, the effects of indomethacin appear to be dependent on the rate of administration [2,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors such as significant PDA, clinical sepsis, and apnoea, which were more prevalent in the CEF group, may serve as a possible explanation. These comorbidities can impair mesenteric blood flow and hence may be detrimental to feeding [27]. The group initiated on exclusive enteral feeding had less apnoea, thus indicating that the increased feeding did not produce more apnoea.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical consequences of persistent PDA are related to the degree of left-to-right shunting through the ductus and diastolic steal, leading to a redistribution of blood flow to the organs with localised vasoconstriction, reduced perfusion to the brain, gut and kidney, and Inhibiting prostaglandin synthesis with non-selective blockers of both cyclo-oxygenases 1 and 2 seems effective for the non-surgical closure of patent ductus and, since 1976, indomethacin (INDO) has been widely used with a reported efficacy of 70%-80% [9,12]. Its use raises some concern, however, regarding cerebral, gastrointestinal and renal perfusion [2,4,6,21,22], since INDO causes a decline in cerebral blood flow (CBF) velocity, reduces mitochondrial oxygenation and disrupts cerebrovascular control [7]. Moreover, side-effects such as necrotising enterocolitis or isolated bowel perforation, oliguria and transient renal failure may be encountered [10].…”
Section: Introductionmentioning
confidence: 99%